Optimal Biomaterial Selection For Anastomosis Device For AV Fistula Surgery Using Multi-Criteria Decision Making Method - Raut, Abhijeet; Uddanwadikar, Rashmi; Padole, Pramod (Journal of Neonatal Surgery, 2025)
Arteriovenous fistula (AVF) failure remains a critical challenge in hemodialysis access, with 30–60% of cases failing due to anastomotic complications. This study employs Multi-Criteria Decision Making (MCDM) through the Analytic Hierarchy Process (AHP) to evaluate and compare implant-grade silicone with Nitinol and ePTFE based on existing literature. Five weighted criteria—biocompatibility (30%), mechanical performance (25%), endothelialization (20%), manufacturing feasibility (15%), and thrombogenicity (10%)—were used for systematic assessment. Literature-derived scores yielded a total AHP score of 8.1 for silicone, surpassing Nitinol (6.2) and ePTFE (4.5). Published in vitro and in vivo findings were analyzed to confirm silicone’s superior hemocompatibility and patency rates. These results demonstrate that silicone is a highly promising candidate for anastomotic device development in AVF surgery and present a reproducible framework for evidence-based biomaterial selection.